Karakteristik dan Persepsi Wisatawan Terhadap Daya Tarik Wisata Kampoeng Anggrek, PT. Anugerah Anggrek Nusantara, Kediri - Illia Seldon Maghfiroh; Rofiu Sisil Annisa (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2023)
AAN continues to develop its company, namely the Kampoeng Anggrek tour. Due to the Covid-19 pandemic, PT. AAN must put more effort into branding Kampoeng Anggrek tourism to the community.The purpose of this research is know the characteristics and perceptions and motivations that influence tourist visits which can indirectly provide an evaluation of the development of PT AAN and support the construction of facilities as a tourist attraction.The research was conducted in dusun Sumber Petung, Sempu Village, Ngancar District, Kediri Regency, East Java involving 30 respondents, namely tourists who visited Kampoeng Anggrek.The factor variables tested in the study were compiled by theoretical and variable synthesis and the data were processed using the scoring method after being measured based on a Likert scale. The results obtained from the characteristics of Kampoeng Anggrek tourism tourists based on age class were dominated by the age of 35-50 years, based on origin dominated by tourists from outside Kediri, based on gender dominated by women, based on visit times dominated by newcomers, based on visiting partners dominated by family groups, and based on objects that tourists like are dominated by tourist objects in the orchid gallery.While the perception and influence of tourist motivation shows thatthese aspects have a positive effect on Kampoeng Anggrek. This makes a plus point for PT. AAN to continue to develop Kampoeng Anggrek tourism which is getting better after the covid-19 pandemic has passed.